Evaluation of carbon fiber and p-aramid composite for industrial helmet using simple cross-ply for protecting human heads. (December 2019) - Kim, Sanghyun; Lee, Jaewoong; Roh, Changhyun; Eun, Jonghyun; Kang, Chankyu
Highlights: We synthesize carbon fiber/ p-aramid reinforced composites by using a simple cross-ply method for manufacturing industrial helmet. Carbon / aramid fiber reinforced composite compared with ABS plastic. The impact energy absorption of p-aramid / carbon fiber reinforced composite was superior to ABS plastic. Both CFRP and CF / AFRP specimens showed good heat resistance. CF / AFRP can be used as a substitute material for ABS plastic because of its excellent mechanical and thermal properties. Abstract: Using personal protective equipment, such as safety helmets, at industrial sites, is the last method to prevent disasters, and such equipment are widely recognized as consumables. Among them, industrial safety helmets use ABS (acrylonitrile butadiene styrene) or PE (polyethylene) resins as the main material of the shell to absorb shocks, and they also possess a relatively good heat resistance. However, efforts to develop new materials by a simple fabrication method are not actively performed. In this study, to improve the safety performance of industrial helmets, an epoxy resin was used as a matrix to produce a p-aramid/carbon fiber composite as a simple cross-ply, and compared to p-aramid fiber-reinforced composites, carbon fiber-reinforced composites, and ABS plastic. The specimens were prepared by the compression molding method, and their mechanical properties including the impact strength, tensile strength, flexural strength, and inter-laminar shear strength along with heat resistance properties were observed via thermogravimetric analysis.